Development of a Telegram Chatbot as a Medium for Public Information Services and Community Complaints at the Sukabumi City Police Resort - Putri Maharani, Adinda Clara (Society : Jurnal Pengabdian Masyarakat, 2026)
The delivery of public services at the Sukabumi City Police Resort faces challenges regarding transparency, accessibility, and responsiveness, particularly in administrative workflows and complaint handling. Conventional face-to-face services and call centers are often constrained by office hours, physical location, and high call volumes, which can hinder the public's right to information. To address these issues, this community service activity implemented a Telegram-based chatbot developed using Python, the Telegram Bot API, and MongoDB. The implementation method followed a systematic design-oriented approach, including needs identification, system design, development, and rigorous testing. The results show that the chatbot successfully provides automated information on Police Clearance Certificates (SKCK), Driving Licenses (SIM), and lost-item reports, while facilitating two-way communication for non-emergency complaints. Additionally, the system integrates a redirection feature to the 110 emergency hotline to ensure urgent reports are handled appropriately. In conclusion, the Telegram chatbot serves as an effective digital interface that enhances service efficiency, reduces manual workloads for officers, and improves public access to police services through a user-friendly and 24-hour accessible platform.